Letramento crítico e ensino de espanhol no ensino médio integrado: questões teórico-práticas no contexto dos Institutos Federais - Benedini, Larissa Cristina Arruda de Oliveira (Universidade Federal de São Carlos, 2019)
“The formation of a critical reader able to go beyond text decoding” (BRASIL, 2015, p. 9) is a concern that is present in both the documents that guide foreign language teaching in high school (BRASIL, 2006) and in the foreign language textbook itself (PNLD 2015 and 2018). We understand that the formation of this critical reader, following the principles of critical literacy, meets the assumptions for foreign language teaching in a comprehensive vocational secondary education as provided in the documents that guide the high school integrated in the Federal Network. However, our perception as a Spanish teacher at a Federal Institute of Education is that there is a mismatch between theory and practice in the curricular attitude of teachers. Taking into account the importance of the critical debate on the concept of literacy (Soares, 2014; Street, 2014; Baptista 2010; Cassany, 2006 and 2010; Monte Mór, 2015; Duboc, 2012) for the field of foreign language teaching in Brazil, the aim of this research is to understand which conceptions about critical literacy and critical reader are currently produced by the theoretical field and how such conceptions are appropriated by a group of Spanish teachers, seeking to identify which evidence in their Spanish teaching practices show the transposition of these conceptions. In addition, it intends to analyze the “curricular attitude” (DUBOC, 2012) of these teachers in the gaps (DUBOC, 2012) of Spanish textbooks. For this, we proceeded to a bibliographical revision about the notion of literacy in national and international scientific productions and in documents that guide the Spanish teaching in Brazil and the PNLD LEM 2015 and 2018. Subsequently, we elaborated an online questionnaire in order to identify conceptions of Spanish teachers group from Federal Institutes. With these data, we conducted interviews with a part of these teachers, in order to deepen our analysis of the “curricular attitude” (DUBOC, 2012) of these teachers, the concept of literacy in their teaching practices using a textbook whose proposal starts from the idea of forming a critical reader in Spanish language and considers the critical literacy as theoretical principle. The analyzes showed that teachers have different conceptions about critical literacy and do not fully take advantage of the “gaps” that could allow the effective formation of the critical reader in Spanish, which seems to confirm our hypothesis that the implementation of critical literacy, as proposed in theoretical field, it depends more on the curricular attitude of the teacher than on what the textbook or curriculum documents offer as a work suggestion. We conclude, therefore, that it is necessary to strengthen the relationship between theories and practices in order to reduce the mismatch between what official documents, textbooks, linguistic research and the teaching practices of the teacher express. The choice of critical literacy as a perspective for Spanish language teaching in high school integrated to the technical in the Federal Network, whether or not integrated with other approaches to language teaching, fully meets the principles of education desired for this type of education.
Critical literacy and teaching spanish in integrated high school: theoretical-practical issues in the contexts of Federal Institutes
Keywords: Leitor crítico; Letramento crítico; Ensino de espanhol; Ensino médio integrado ao técnico; IFs; Critical reader; Critical literacy; Spanish teaching High school integrated with the technician; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA